Molecular Study of Adenovirus Genotypes 40 and 41 in Children with Acute Gastroenteritis - Essa, Sara G.; Zaki, Maysaa E. S.; Elmansoury, Eman A.; Hassan, Rasha H.; EL Kheir, Nermin Y.A. (Infectious Disorders - Drug Targets, 2022)
Background: Adenovirus is a common virus associated with acute gastroenteritis in children. There are certain genotypes that are prevalent in these infections, such as genotypes 40 and 41. Objective: The aim of the present study was to investigate the incidence of adenovirus genotypes 40 and 41 in children with acute gastroenteritis by polymerase chain reaction (PCR) and also to determine the possibility of Adenovirus co-infections with Rotavirus. Methods: The study was a cross-sectional study that included 100 children with acute gastroenteritis. The children were subjected to full history taking and clinical examination. Stool samples from the patients were subjected to detection of adenovirus and rotavirus antigens by enzyme-linked immunosorbent assay (ELISA) and detection of adenovirus genotypes 40 and 41 by polymerase chain reaction (PCR). Results: The most prevalent virus by the used methods was rotavirus antigen in the stool (35%). Adenovirus antigen detection was positive in 23% of the stool samples, with positive PCR for these samples in 22%. The ADv40 was detected in 13 samples, and ADv41 was detected in 9 samples. One positive sample by adenovirus antigen ELISA was negative by PCR for these genotypes. Mixed rotavirus and adenovirus by ELISA were detected in 7% of the children. In patients with positive adenovirus antigen by ELISA, the most common symptoms were vomiting (54.5%) and abdominal pain (45.5%). An insignificant difference between fever (P=0.94) and abdominal pain (P=0.63) was detected in children infected with adenovirus compared to patients infected with other organisms. The adenovirus was detected in 68.2% of children with acute gastroenteritis ≤ 24 months. Vomiting was significantly increased in children with adenovirus (54.5%) compared to children negative for adenovirus (23.1%-P=0.004, OR 4.0, 95%CI: 1.5-10.8). Conclusion: The study highlights the presence of adenovirus genotypes 40 and 41 in the stool of children with acute gastroenteritis. Combined rotavirus and adenovirus infections were detected in our study.
Keywords: adenovirus 41